10x + 2y + 8z - 5x + 4z - 4y
= 10x - 5x + 2y - 4y + 8z + 4z
= (10 - 5)x + (2 - 4)y + (8 + 4)z
= 5x - 2y + 12z
x2 + 10x + 21 = (x + 3)(x + 7)
x + 13x + 10x = 50 - 6
5x + 4 = 10x - 5 10x - 5x = 4 + 5 5x = 9 x = 1.8
6-x+12 = 10x+7 6+12-7 = 10x+x 11 = 11x x = 1
10x+7 = 5x+32 10x-5x = 32-7 5x = 25 x = 5
x2 + 10x + 21 = (x + 3)(x + 7)
x + 13x + 10x = 50 - 6
10x + 3 = 15 10x = 15 - 3 10x = 12 x = 1.2
y=-10x-4
5x + 4 = 10x - 5 10x - 5x = 4 + 5 5x = 9 x = 1.8
6-x+12 = 10x+7 6+12-7 = 10x+x 11 = 11x x = 1
10x+7 = 5x+32 10x-5x = 32-7 5x = 25 x = 5
-10x+3 = -x+12 -10x+x = 12-3 -9x = 9 x = -1
x=-1.6
6.28
10x + 13 = 1710x = 17-1310x = 4x = 4/10x = 0.4
53